COMBINED EFFECT OF STREPTOMYCIN AND SWEET ORANGE ESSENTIAL OIL TO MEMBRANE AND ACROSOME INTEGRITY BOER GOAT FROZEN SEMEN - Sitepu, Sukma Aditya; Marisa, Julia (Universitas Negeri Medan, 2019)
One of factors that cause a bad quality of Boer Goat frozen semen is the growth of bacterial. This can be overcome by adding antibiotics such as streptomycin. To further suppress the growth of bacteria can be added other ingredients that contain antibacterials such as sweet orange essential oil. The purpose of this research is to know the percentage value of Membrane Integrity and Acrosome Integrity on Boer Goat frozen semen with addition sweet orange essential oil and streptomycin. The method used was experimental using Completely Randomized Design with 5 treatments and 5 replications. The treatment in this research is addition 0%, 0,25%; 0.5%; 0.75% and 1% sweet orange essential oil on tris yolk and streptomycin extender. The results showed the best treatment addition combination streptomycin and sweet orange essential oil to percentage Membrane Integrity and Acrosome Integrity is increase 1% sweet orange essential oil.Keywords: Boer Goat, essential oil, frozen semen, streptomycin, sweet orange.